2019
DOI: 10.3389/fonc.2019.00711
|View full text |Cite
|
Sign up to set email alerts
|

Human Polyomavirus JCPyV and Its Role in Progressive Multifocal Leukoencephalopathy and Oncogenesis

Abstract: The human neurotropic virus JCPyV, a member of the Polyomaviridiae family, is the opportunistic infectious agent of Progressive Multifocal Leukoencephalopathy (PML), a fatal disease seen in severe immunosuppressive conditions and, during the last decade, in patients undergoing immunotherapy. JCPyV is a ubiquitous pathogen with up to 85% of the adult population word-wide exhibiting antibodies against it. Early experiments demonstrated that direct inoculation of JCPyV into the brain of dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 205 publications
(217 reference statements)
0
18
0
3
Order By: Relevance
“…The genotyping results for JCPyV and BKPyV were consistent with those of previously published epidemiological studies, which identified genotypes 1 and I, respectively, as the most represented genotypes within the European population. In addition, the presence of a rearranged NCCR JCPyV infecting PML patients has been widely reported in the literature [52]. The four sequenced BKPyV NCCRs showed different rearrangements and point mutations and were classified arbitrarily as variants of the known Dunlop and TU strains [24].…”
Section: Discussionmentioning
confidence: 99%
“…The genotyping results for JCPyV and BKPyV were consistent with those of previously published epidemiological studies, which identified genotypes 1 and I, respectively, as the most represented genotypes within the European population. In addition, the presence of a rearranged NCCR JCPyV infecting PML patients has been widely reported in the literature [52]. The four sequenced BKPyV NCCRs showed different rearrangements and point mutations and were classified arbitrarily as variants of the known Dunlop and TU strains [24].…”
Section: Discussionmentioning
confidence: 99%
“…Our work identified the JCV tAg as a type I IFN antagonist that specifically targets the RIG-I signaling pathway. Since polyomavirus tAgs have been most well characterized in their ability to bind to the cellular protein phosphatase 2A (66,67) or for their oncogenic properties (however, not in the case of JCV tAg) (68,69), our study unveiled a novel function for polyomaviral tAg proteins that may play a major role for virus persistence and disease outcomes.…”
Section: Discussionmentioning
confidence: 87%
“…Notably, the total number of samples tested for hepatitis A and E. coli was 24, and the total number of samples tested for hepatitis A and total coliforms was 15. The highest correlated indicator for norovirus was polyomavirus ( κ = 0.21), which is a human pathogen that causes progressive multifocal leukoencephalopathy (PML) and thus not a useful environmental indicator organism [ 30 ]. The level of agreement between norovirus with adenovirus was 0.09 ( n = 16, 95% CI −0.05, 0.23) which indicates poor agreement.…”
Section: Resultsmentioning
confidence: 99%